Intoxicação por metilmercúrio em baixas doses induz inflamação sistêmica, alterações comportamentais e neuroquímicas em camundongos c57bl6/j adultos - Pinto, Daniel Vieira (2021)
Methylmercury (MeHg) is an organometal with strong neurotoxic action on the central nervous system (CNS). Human contamination by MeHg is mostly due to the consumption of fish, seafood or contaminated water. In the CNS, MeHg can cause neuroinflammation and increased oxidative stress, inducing the death of neurons in the hippocampus. Many studies have documented the harmful effect of MeHg in the hippocampus, but the low-grade and chronic neurotoxicity of MeHg has not yet been evaluated in adult mice with a focus on neurotransmitters, inflammation, oxidative stress in the hippocampus and memory. In this work, adult C57BL6J mice intoxicated with 2mg MeHg / L in drinking water for 30 days and controls were used. Serum concentrations of endotoxin (LPS), TNF-α and myeloperoxidase (MPO) were evaluated as markers of systemic inflammation and total cholesterol and triglycerides to assess dyslipidemia. Hippocampal tissue concentrations of neurotransmitters (glutamate, tyrosine, taurine, gamma-amino butyric acid (GABA) and glycine), acetylcholinesterase activity, gene expression of inflammatory markers (IFN-γ, IL-4, IL-5, IL-6 and IL-10), malondialdehyde (MDA), oxidative stress, MPO and brain-derived growth factor (BDNF). Behavioral tests were carried out in order to assess motor impairment and exploratory behavior (open field), working memory (Y-maze), spatial memory and long-term memory (Barnes maze). The animals' weight was monitored weekly. Intoxicated animals had a greater weight gain. The intoxicated group also had higher serum concentrations of triacylglycerols and total cholesterol (p <0.05) and higher peripheric concentrations of LPS (p = 0.01), TNF-α (p <0.0001) and MPO (p<0,0001) compared to controls. Intoxicated animals had higher hippocampal tissue concentrations of MDA (p = 0.008) and MPO (p <0.05). Gene expression of IL-4 was lower in the intoxicated group (p <0.05) compared to the control group. The concentration of neurotransmitters GABA (p <0.05) and glycine (p <0.0001) was higher in the intoxicated group, with a reduction in the concentration of taurine (p = 0.003), but without changes in the levels of glutamate and tyrosine. Intoxicated animals had the lowest total distance covered (p = 0.02), the lowest average speed (p = 0.02), the lowest rearing records (p = 0.01) and the highest grooming records (p = 0.01) that the group controls in the open field test. There was no significant difference in working, spatial or learning memory. The findings of this study suggest that low-grade MeHg intoxication induces biochemical changes in the hippocampus, with disturbance of inhibitory neurotransmitters associated with dyslipidemia and systemic inflammation, the latter presumably due to changes in the intestinal barrier.